Case Report: Perspective of a Caregiver on Functional Outcomes Following Bilateral Lateral Pectoral Nerve Cryoneurotomy to Treat Spasticity in a Pediatric Patient With Cerebral Palsy - Scobie, Jack; Winston, Paul (Frontiers in Rehabilitation Sciences, 2021)
Spasticity is a common and difficult to manage complication of cerebral palsy that significantly impacts patient function and quality of life.  This case study reports a 15-year-old male with quadriplegic cerebral palsy, GMFCS 5, who presented with significant bilateral adducted and internally rotated shoulders as a component of generalized spasticity.  The patient’s lower limb spasticity had been treated with botulinum toxin A injections; however, the shoulder region was spared due to concerns of toxin spread and aspiration risk. Following diagnostic nerve blocks, the patient underwent bilateral cryoneurotomies of the right and left lateral pectoral nerves lasting 3.5 minutes for each lesion.  One month after the cryoneurotomies, the ROM had improved from 86° to 133° on the right and 90° to 139° on the left.  Improvements in range of motion were retained at 9 months post-procedure. At 8.5 months following the cryoneurotomies, the caregiver reported improvements in upper body dressing, upper body washing, transferring, and the ability of the patient to remain sitting in his wheelchair for extended periods of time.  Cryoneurotomy may be an effective procedure for improving shoulder range of motion and specific functional outcomes for caregivers of patients with spasticity arising from cerebral palsy.